Uji Daya Hambat Madu Randu Terhadap Escherichia coli Secara in vitro - HERMAWATI, ANDYANITA HANIF; Islamy, Aesthetiza (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2023)
A test of the inhibitory power of randu honey against Eschericia coli ATCC 8739 has been carried out. Honey contains compounds that function as antibacterials. The honey used is monoflora honey, namely randu honey. The concentration of randu honey in the inhibitory power test against Escherichia coli ATCC 8739 is 100% and 50%. The method used is the diffusion method in order to use nutrient media. The inhibitory power of randu honey with a concentration of 100% against Escherichia coli ATCC 8739 is 39.30 mm and the randu honey solution with a concentration of 50% against Escherichia coli ATCC 8739 is 35.80 mm so that randu honey has the potential to be antibacterial.